2022
DOI: 10.11604/pamj.2022.42.244.34337
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of metaphyseal osteonecrosis of humerus in a post covid patient: a case report

Abstract: Osteonecrosis of the metaphysis is often rare as it is a highly vascular region. Here we report an unusual case of non-traumatic osteonecrosis of the humerus predominantly involving the metaphysis in a post covid elderly female. The patient had a pathological fracture of humerus during the post-operative period of intertrochanteric femur fracture surgery. She was evaluated for the causes of pathological fracture and the fracture was managed with hemi replacement of the shoulder because of the extensive bone lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…When CCS were used, ON had an early onset as usually reported [34]. Thankappan et al [35] described an unusual case of atraumatic osteonecrosis of the proximal humerus metaphysis. The metaphyseal area is richly vascularized and necrosis in this area is quite rare.…”
Section: Discussionmentioning
confidence: 89%
“…When CCS were used, ON had an early onset as usually reported [34]. Thankappan et al [35] described an unusual case of atraumatic osteonecrosis of the proximal humerus metaphysis. The metaphyseal area is richly vascularized and necrosis in this area is quite rare.…”
Section: Discussionmentioning
confidence: 89%
“…34 After the COVID-19 pandemic, there are some case reports and case series of AVN related to COVID-19. [11][12][13][14][15][16][17][18][19][20][21] In COVID-19 patients, multiple mechanisms, such as endothelial dysfunction, clot formation, and corticosteroid consumption, may occur simultaneously, which all lead to bone infarct or osteonecrosis. The prevalence of AVN related to COVID-19 was reported to be around 0.07%.…”
Section: F I G U R Ementioning
confidence: 99%
“…It seems that in COVID‐19 patients, multiple mechanisms, such as endothelial dysfunction, clot formation, and corticosteroid consumption, may occur simultaneously, which all lead to bone infarct or osteonecrosis. There are some case reports of AVN related to COVID‐19 around the world 11–21 . Data have shown that AVN in COVID‐19 develops in shorter time compared with this pathology in patients without COVID‐19 22 .…”
Section: Introductionmentioning
confidence: 99%